An insight into the autonomic and haemodynamic mechanisms underlying reflex syncope in children and adolescents: a multiparametric analysis. (23rd June 2014) - Laranjo, Sérgio; Tavares, Cristiano; Oliveira, Mário; Trigo, Conceição; Pinto, Fátima; Rocha, Isabel
Abstract Around 15% of children and adolescents experience at least one episode of syncope until adulthood. Excluding cardiac disease, the majority of syncopes are of reflex origin and benign in nature. In this situation, a tilt test is conducted to reproduce symptoms and to evaluate cardiovascular adaptations to orthostatism, but its mechanisms are not yet well defined. Here, we investigated haemodynamics and autonomic activity during tilt in young patients. Patients (n=113) with unexplained syncope were enrolled. Tilt followed a standard protocol without provocative agents. A positive response (fainters) was defined as a sudden development of syncope or presyncope associated with hypotension, bradycardia, or both. Haemodynamic parameters, autonomic activity, and baroreflex sensibility were evaluated. Data were analysed on baseline; immediately after tilting; on tilt adaptation; before fainting or before tilt-down for non-fainters; and on tilt-down. A total of 45 patients experienced syncope after a mean time of 18 minutes. During tilting up, fainters showed lower blood pressure and peripheral resistance values, which decreased progressively with time together with baroreflex sensibility. Sympathetic tone increased massively along time till syncope. No changes in cardiac output and heart rate were observed. Results show a strong effort of the autonomic nervous system to adapt to orthostatic stress through different magnitudes of sympathetic output, which was maximal before syncope without apparent modifications of parasympathetic tone. These changes suggest an imbalance between both branches of the autonomic nervous system, not enabling a time-progressive adaptation and leading the subject to faint.